Alternative Food Networks An Interdisciplinary Assessment (Springer International Publishing, 2018)
In recent years, Alternative Food Networks (AFNs) have been a key issue both in the scientific community and in public debates. This is due to their profound implications for rural development, local sustainability, and bio-economics. This edited collection discusses what the main determinants of the participation of operators - both consumers and producers - in AFNs are, what the conditions for their sustainability are, what their social and environmental effects are, and how they are distributed geographically. Further discussions include the effect of AFNs in structuring the food chain and how AFNs can be successfully scaled up. The authors explicitly take an interdisciplinary approach to analyse AFNs from different perspectives, using as an example the Italian region of Piedmont, a particularly interesting case study due to the diffusion of AFNs in the area, as well as due to the fact that it was in this region that the 'Slow Food' movement originated. Alessandro Corsi is Associate Professor of Agricultural Economics at the University of Turin, Italy. Filippo Barbera is Associate Professor of Economic Sociology at the University of Turin, Italy and Affiliate of the Collegio Carlo Alberto, Turin, Italy. Egidio Dansero is Professor of Political and Economic Geography at the University of Turin, Italy. Cristiana Peano is Associate Professor of Arboriculture at the University of Turin, Italy.